Research trend and hotspots of polycystic ovary syndrome with depression from 1993 to 2024: a bibliometric analysis - Xie, Jing; Cao, Yi; Wen, Qian; Song, Xuxia; Shi, Yuanyuan; Gao, Xia (Frontiers in Global Women's Health, 2024)
BackgroundPolycystic ovary syndrome (PCOS), a common endocrine disorder, affects women of reproductive age, and its adverse consequences affect women throughout their lifespan, from adolescence to postmenopause. The prevalence of depression is much higher in women with PCOS than in healthy controls. Thus, it is recommended that depressive syndrome be screened routinely in all patients with PCOS at diagnosis. To date, no comprehensive bibliometric analysis has been conducted in this field. Therefore, we conducted a bibliometric analysis to describe the current status, trends, and hotspots of PCOS research related to depression.Materials and methodsUsing data retrieved from the Web of Science (WoS) Core Collection database from 1993 to 2024, bibliometric analyses were performed using WoS and CiteSpace software.ResultsSince the first paper was published in 1993, studies related to PCOS and depression have remained rare in the following decade. Since the establishment of the Rotterdam criteria in 2003, research on the etiology, pathogenesis, and treatment of PCOS with depressive syndrome has entered a booming period. The United States and Australia indisputably took leading positions in this area, with the most outstanding institutions in the world being the University of Pennsylvania and Monash University. Although achievements have flourished since 2003, the exact pathogenesis of PCOS remains uncertain owing to its heterogeneity. New research is rapidly increasing to fill these gaps and to push forward the goal of improving the quality of life in women with PCOS and depression. Along with progress in research, the world's leading societies organize conferences every 5 years to update guidelines for the assessment and management of PCOS. “Oxidative stress,” “inflammation,” “obstructive sleep apnea,” “gut microbiota,” and “single nucleotide polymorphism” appeared as new hotspots in the recent 5 years.ConclusionA bibliometric analysis was performed to describe the trends and hotspots of research in women with PCOS and depression to attract the attention of more researchers to this topic.Systematic Review Registrationhttps://www.webofscience.com/wos/woscc/basic-search.